2004
DOI: 10.1269/jrr.45.105
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Induction of Telomere Instability in Normal Human Fibroblast Cells by Ionizing Radiation

Abstract: We examined the delayed induction of telomere instability in hTERT-immortalized normal human fibroblast (BJ1-hTERT) cells exposed to X-rays. BJ1-hTERT cells were irradiated with 2 Gy of X-rays, and chromosome aberrations were analyzed 24 hours after irradiation and in the surviving cells 14 days after X-ray exposure. We found that the X-ray-surviving cells showed an increased frequency of chromatid gaps and breaks and chromosome fragments compared to the control cells. Furthermore, centromere- and telomere-FIS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
18
0
6

Year Published

2006
2006
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 22 publications
6
18
0
6
Order By: Relevance
“…The right panel shows a photograph of representative TRAP assay result for HUVECs after X-irradiation. The materials used for the pc positive control and nc negative control were provided with the kit leads to telomere reorganization (these hypotheses are partly supported by the results of previous studies [23,24]; a 0.5-Gy dose of IR not only induced telomeric changes but maintained apoptotic rate, leading to the growth suppression of the normal HUVECs.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The right panel shows a photograph of representative TRAP assay result for HUVECs after X-irradiation. The materials used for the pc positive control and nc negative control were provided with the kit leads to telomere reorganization (these hypotheses are partly supported by the results of previous studies [23,24]; a 0.5-Gy dose of IR not only induced telomeric changes but maintained apoptotic rate, leading to the growth suppression of the normal HUVECs.…”
Section: Discussionmentioning
confidence: 72%
“…These findings suggest an inverse relationship between telomere length and chromosomal radiosensitivity [11]. Furthermore, X-rays alter chromosomal organization by affecting telomere stability after irradiation as a delayed effect in X-ray-surviving cells [23], which supports our results showing a persistent apoptotic rate in the late stage, and a relatively obvious change in the shortest telomeres among the irradiated cells over the observation period after IR, particularly from the third day to the fourth day; such changes were not observed in other sizes of telomeres.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, most dicentrics that arise in the cells more than 30 generations postirradiation (nontargeted aberrations) are not accompanied by fragments (23). We previously showed that these types of dicentrics without fragments are formed by telomeric end-to-end fusions induced by the nontargeted effect of radiation (13,15). This again suggests the possibility that the pathway leading to the formation of nontargeted aberrations differs from that for targeted aberrations.…”
Section: Discussionmentioning
confidence: 97%
“…We previously demonstrated that radiation destabilized telomere function, which promoted persistent chromosome instability in immortalized mouse (13,14) and human cells (15), suggesting that telomeres may be susceptible to the induction of genomic instability. Therefore, we speculate that telomere destabilization is a possible mechanism by which the memory of irradiation is retained.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation